Nephrin is necessary for podocyte recovery following injury in an adult mature glomerulus. - Rakesh Verma; Madhusudan Venkatareddy; Anne Kalinowski; Theodore Li; Joanna Kukla; Ashomathi Mollin; Gabriel Cara-Fuentes; Sanjeevkumar R Patel; Puneet Garg (PLoS ONE)
Nephrin (Nphs1) is an adhesion protein that is expressed at the podocyte intercellular junction in the glomerulus. Nphs1 mutations in humans or deletion in animal genetic models results in a developmental failure of foot process formation. A number of studies have shown decrease in expression of nephrin in various proteinuric kidney diseases as well as in animal models of glomerular disease. Decrease in nephrin expression has been suggested to precede podocyte loss and linked to the progression of kidney disease. Whether the decrease in expression of nephrin is related to loss of podocytes or lead to podocyte detachment is unclear. To answer this central question we generated an inducible model of nephrin deletion (Nphs1Tam-Cre) in order to lower nephrin expression in healthy adult mice. Following tamoxifen-induction there was a 75% decrease in nephrin expression by 14 days. The Nphs1Tam-Cre mice had normal foot process ultrastructure and intact filtration barriers up to 4-6 weeks post-induction. Despite the loss of nephrin expression, the podocyte number and density remained unchanged during the initial period. Unexpectedly, nephrin expression, albeit at low levels persisted at the slit diaphragm up to 16-20 weeks post-tamoxifen induction. The mice became progressively proteinuric with glomerular hypertrophy and scarring reminiscent of focal and segmental glomerulosclerosis at 20 weeks. Four week-old Nphs1 knockout mice subjected to protamine sulfate model of podocyte injury demonstrated failure to recover from foot process effacement following heparin sulfate. Similarly, Nphs1 knockout mice failed to recover following nephrotoxic serum (NTS) with persistence of proteinuria and foot process effacement. Our results suggest that as in development, nephrin is necessary for maintenance of a healthy glomerular filter. In contrast to the developmental phenotype, lowering nephrin expression in a mature glomerulus resulted in a slowly progressive disease that histologically resembles FSGS a disease linked closely with podocyte depletion. Podocytes with low levels of nephrin expression are both susceptible and unable to recover following perturbation. Our results suggest that decreased nephrin expression independent of podocyte loss occurring as an early event in proteinuric kidney diseases might play a role in disease progression.